Nursing Research Contributes to Changes in Clinical Practice - Oe, Makoto (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Through my experience visiting Hazanuddin University and touring the hospitals in Makassar, I reconsidered the role of nursing research in the development of nursing technology. It will be increasingly important to train professionals to provide quality care, develop new nursing techniques through interdisciplinary research and industry-academia collaboration, and establish evidence regarding insurance reimbursement.